Evaluation of Event-Free Survival Surrogating Overall Survival as the Endpoint in Neoadjuvant Clinical Trials of Gastroesophageal Adenocarcinoma - Liu, Hua; Wang, Yakun; Qi, Changsong; Xie, Tong; Peng, Zhi; Li, Jian; Shen, Lin; Zhang, Xiaotian (Frontiers in Oncology, 2022)
Background: Gastric cancer (GC) is one of the most common malignant cancers worldwide. The development of potential antitumor agents is being investigated and stimulates more clinical trials. Overall survival (OS) is consistently considered the primary endpoint for clinical trials on treatment effect assessment. However, finding an appropriate endpoint more sensitive and easy for trials is vital. For adjuvant chemotherapy, current evidence has shown that disease-free survival(DFS) could be a surrogate endpoint for randomized controlled trials (RCTs) with gastric cancer, evidence for neoadjuvant chemotherapy (NCT) or chemoradiotherapy (NCRT) is inadequate, and adverse conclusions have been drawn in published studies. This study was designed to evaluate the possibility that event-free survival(EFS) surrogate OS in randomized controlled trials of NCT/NCRT of gastric and gastroesophageal (GC or GEJ) adenocarcinoma patients (ADK). Methods: A literature search was conducted through databases including PubMed, the Cochrane Library and Embase. References and articles from other sources were also included. 8 RCTs with 2837 patients were eventually analyzed. Hazard ratios of OS and EFS was directly approached. Surrogacy of EFS was assessed through the correlation of determination R2. We used Review Manage pooling hazard ratios of OS and EFS at trial level. I2 was used to demonstrate the heterogeneity of inclusions. Publication bias was summarized and illustrated through funnel plots. All analyses were two sides with setting statistical significance as p<0.05. Results: Eight RCTs of 2837 patients were analyzed at the trial level. The I2 for OS was 21% and 51% for FES, and a fixed effect model was used. The pooled HR of OS was 0.83 (95% CI: 0.75-0.92, p<0.001), and that of EFS was 0.78 (95% CI: 0.71-0.86, p<0.001). The regression correlation coefficient between EFS and OS was 0.76 (95% CI: 0.41-1.11, p=0.002), and the coefficient of determination R2=0.826 (p=0.028). Conclusions: A strong correlation was observed between overall survival and event-free survival at the trial level. Event-free survival could be a surrogate endpoint for neoadjuvant randomized controlled trials of gastric and gastroesophageal adenocarcinoma. Further studies and evidence from individual data are expected.